Negative electrode material and preparation method thereof, negative electrode plate, electrochemical device and electric device

By using a cladding structure in the negative electrode material of sodium ion battery, including sodium supplementation agent, conductive agent and amorphous carbon, the irreversible loss and reaction problems of sodium ion battery during the first charge and discharge are solved, and the battery cell is significantly improved Energy density and charge and discharge efficiency.

CN119315000AActive Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310854125.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

Existing sodium ion batteries have severe irreversible sodium losses during the first charge and discharge, resulting in low energy density and charge and discharge efficiency of the battery cell. In addition, irreversible reactions are prone to occur when the negative electrode active material comes into contact with the electrolyte, which reduces the battery cell performance.

Method used

Design of negative electrode material, in which the core is composed of negative electrode active material, the cladding layer includes sodium supplementation agent, conductive agent, amorphous carbon and boron-containing compounds, protecting the core by partial or complete cladding to reduce direct contact with the electrolyte , improve sodium supplement efficiency and conductivity.

Benefits of technology

It effectively reduces irreversible sodium consumption, improves the first charge and discharge efficiency and cycle performance of the battery cell, and improves the energy density and rate performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315000A_ABST
    Figure CN119315000A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a preparation method thereof, a negative electrode plate, an electrochemical device and an electric device. The negative electrode material comprises an inner core and a coating layer at least partially coating the surface of the inner core, the material of the inner core comprises a negative electrode active material, and the material of the coating layer comprises a sodium supplementing agent. The surface of the inner core comprising the negative electrode active material is at least partially coated with the sodium supplementing agent, so that on one hand, irreversible sodium loss of first charging and discharging can be made up through the sodium supplementing agent, consumption of a sodium source is reduced, and the first efficiency and cycle performance of the battery cell are improved; and on the other hand, through at least partial coating of the sodium supplementing agent, direct contact between the negative electrode active material and the electrolyte can be reduced, so that irreversible reaction between the negative electrode active material and the electrolyte is reduced, and the energy density and the first charge-discharge efficiency of the battery cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet, an electrochemical device and an electrical device. Background Art

[0002] In order to meet the fast charging performance of new energy vehicles, many energy materials with high energy density and fast charging performance have been developed one after another. Among them, sodium-ion batteries are regarded as one of the substitutes for lithium-ion batteries due to their abundant sodium resources, low price and superior safety performance.

[0003] In order to reduce the irreversible sodium loss during the first charge and discharge and improve the energy density of the battery, sodium replenishment has become a research focus. However, the conventional sodium replenishment method is mainly aimed at the sodium replenishment of the positive electrode active material, which has no obvious effect on improving the fast charging performance, and has problems such as low first efficiency and poor cycle performance. In addition, when the negative electrode active material comes into contact with the electrolyte, some of the negative electrode active materials undergo irreversible reactions, producing inert materials that cannot participate in electron transmission, reducing the proportion of negative electrode active materials, thereby reducing the energy density and first charge and discharge efficiency of the battery. Summary of the invention

[0004] The present application is made in view of the above-mentioned issues, and its purpose is to provide a negative electrode material to compensate for the irreversible sodium source consumption during the initial charge and discharge process, improve the initial efficiency and cycle performance of the battery cell, and reduce the probability of irreversible reactions of the negative electrode material.

[0005] In order to achieve the above-mentioned objectives, the embodiments of the present application provide a negative electrode material and a preparation method thereof, a negative electrode sheet, an electrochemical device and an electrical device.

[0006] In a first aspect, an embodiment of the present application proposes a negative electrode material, comprising a core and a coating layer at least partially coating the surface of the core, wherein the material of the core comprises a negative electrode active material, and the material of the coating layer comprises a sodium supplement.

[0007] Therefore, in the technical solution of the embodiment of the present application, by at least partially coating the surface of the inner core including the negative electrode active material with the sodium supplement, on the one hand, the irreversible sodium loss of the first charge and discharge can be compensated by the sodium supplement, the consumption of the sodium source can be reduced, and the first efficiency and cycle performance of the battery cell can be improved. On the other hand, by at least partially coating the sodium supplement, the direct contact between the negative electrode active material and the electrolyte can be reduced, thereby reducing the irreversible reaction between the negative electrode active material and the electrolyte, thereby improving the energy density and the first charge and discharge efficiency of the battery cell. In some embodiments of the present application, the coating layer may be partially coated on the surface of the inner core; in other embodiments of the present invention, the coating layer may be completely coated on the surface of the inner core. At this time, the coating layer has a better protective effect on reducing the direct contact between the inner core negative electrode active material and the electrolyte.

[0008] In any embodiment, the material of the coating layer also includes at least one of a conductive agent, amorphous carbon and a boron-containing compound. By adding a conductive agent to the material of the coating layer, multiple conductive channels can be formed in the coating layer, the transmission efficiency of sodium ions in the sodium supplement material is improved, and additional electron channels are provided for the negative electrode active material in the core, thereby improving the transmission efficiency of electrons, and thus improving the rate performance of the battery cell. By adding amorphous carbon to the material of the coating layer, a large-area conductive channel can be formed in the entire coating layer, the transmission efficiency of sodium ions in the sodium supplement material is improved, and electron channels are provided for the negative electrode active material in the core, thereby improving the transmission efficiency of electrons, and thus improving the rate performance of the battery cell. By adding a boron-containing compound to the coating layer material, the catalytic properties of the boron-containing compound can be utilized to improve the ability of the sodium supplement agent to release sodium ions at a lower potential, thereby improving the sodium supplement efficiency of the negative electrode material, thereby improving the first charge and discharge efficiency. In some embodiments of the present application, the material of the coating layer may include only any one of a conductive agent, amorphous carbon, and a boron-containing compound. In some embodiments of the present application, the material of the coating layer also includes two or more of a conductive agent, amorphous carbon, and a boron-containing compound. In some embodiments of the present application, the coating layer can be a mixed layer, and the material of the mixed layer includes a sodium supplement and also includes a conductive agent, amorphous carbon, and at least one of a boron-containing compound. In some embodiments of the present application, the coating layer can also be a multilayer, for example, the material of the middle layer includes a sodium supplement, and the material of the outer layer includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound.

[0009] It should be noted that when the material of the coating layer includes a conductive agent, in some embodiments of the present application, the specific type of the conductive agent is not limited, as long as multiple conductive channels can be formed to provide channels for the transfer of sodium ions and electrons. For example, the conductive agent can be carbon nanotubes, graphene or conductive carbon black. When the material of the coating layer includes amorphous carbon, in some embodiments of the present application, the material of the coating layer may only contain amorphous carbon and sodium-supplementing materials. In other embodiments of the present application, the material of the coating layer may simultaneously contain amorphous carbon, a conductive agent and a sodium-supplementing material. When amorphous carbon, a conductive agent and a sodium-supplementing material are simultaneously contained, a plurality of conductive channel points can be provided while providing a large area of ​​conductive channels for the coating layer. The combination of the conductive channel surface and the conductive channel point can further improve the transmission efficiency of sodium ions in the sodium-supplementing material, provide enough electron channels for the negative electrode active material in the inner core, further improve the transmission efficiency of electrons, and thus improve the rate performance of the battery cell. In some embodiments of the present application, the specific type of the amorphous carbon is not limited, as long as it can form a large-area conductive channel to provide a surface channel for the transfer of sodium ions and electrons. For example, the amorphous carbon can be epoxy resin, asphalt, phenolic resin, gelatin, furfural resin, etc.

[0010] In any embodiment, the coating layer includes an intermediate coating layer and an outer coating layer sequentially arranged from the inner core to the outer core, wherein the material of the intermediate coating layer includes a sodium supplement, and the material of the outer coating layer includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound. By setting the sodium supplement as the intermediate coating layer and at least one of the conductive agent, amorphous carbon, and a boron-containing compound as the outer coating layer, the sodium supplement can be protected under the premise of reducing the direct contact between the inner core negative electrode active material and the electrolyte, reducing the direct contact between the sodium supplement and the electrolyte, and improving the sodium supplement effect. At the same time, since the outer coating layer includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound, the sodium supplement performance of the sodium supplement can be improved. In some embodiments of the present application, the material of the outer coating layer may include only any one of a conductive agent, amorphous carbon, and a boron-containing compound. In some embodiments of the present application, the material of the outer coating layer may include two or more of a conductive agent, amorphous carbon, and a boron-containing compound.

[0011] In any embodiment, the conductive agent includes at least one of conductive carbon black, carbon nanotubes and graphene. The conductive channel formed by at least one of conductive carbon black, carbon nanotubes and graphene has better conductivity and is more effective in improving the rate performance of the battery cell; and / or,

[0012] In any embodiment, the amorphous carbon includes at least one of epoxy resin, phenolic resin and furfural resin. Using at least one of epoxy resin, phenolic resin and furfural resin can reduce the cost of the coating layer on the basis of providing a conductive channel surface; and / or,

[0013] In any embodiment, the boron-containing compound includes at least one of titanium diboride, magnesium diboride, zirconium diboride and tungsten boride. Using at least one of titanium diboride, magnesium diboride, zirconium diboride and tungsten boride can provide better catalytic performance, further improve the ability of the sodium supplement agent to release sodium ions at a lower potential, thereby improving the sodium supplement efficiency of the negative electrode material, thereby improving the initial charge and discharge efficiency.

[0014] In any embodiment, the particle size of the boron-containing compound is 50-500nm. The particle size of the boron-containing compound affects its catalytic performance. When the particle size is less than 50nm, the particles are small, and the boron-containing compound is easy to agglomerate, which reduces its own dispersion performance and thus affects the catalytic effect. When the particle size is greater than 500nm, the particles are large and the specific surface area is small, which reduces its own catalytic performance; optionally, the particle size of the boron-containing compound is 100-200nm.

[0015] In any embodiment, the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon, wherein the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon in a mass ratio of (0.5-10):(0.5-10):(0.1-5):100. When the material of the coating layer contains a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon at the same time, a suitable mass ratio can improve the sodium supplement The ability of the agent to release sodium ions at a lower potential, thereby improving the sodium supplement efficiency of the negative electrode material, providing a conductive channel and a conductive surface for sodium ions and electrons, thereby improving the initial charge and discharge efficiency and improving the rate performance. When the mass ratio of the sodium supplement is less than 0.5, the proportion is too small, and the sodium supplement effect decreases. When the mass ratio of the sodium supplement is greater than 10, the sodium supplement occupies more volume, squeezing the proportion of other components, and the extra sodium supplement cannot be used, reducing the energy density of the battery cell. When the mass ratio of the conductive agent is less than 0.5, the conductive channel points are too few, and the improvement rate of the conductive performance is low. When the mass ratio of the conductive agent is greater than 10, the conductive agent is too much, and the volume occupied by the conductive agent is too large, squeezing the proportion of other components, and the extra conductive agent cannot be used, squeezing the proportion of other components. When the mass ratio of the boron-containing compound is less than 0.1, the content of the boron-containing compound is low, the catalytic effect is weak, and the catalytic performance decreases. When the mass ratio of the boron-containing compound is greater than 5, the boron-containing compound is too much, and the volume occupied by the boron-containing compound is too much, squeezing the proportion of other components, and the extra boron-containing compound cannot be used, reducing the energy density of the battery. Optionally, the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon in a mass ratio of: (1-5): (1-5): (0.5-2): 100.

[0016] In any embodiment, the mass proportion of the negative electrode active material in the negative electrode material is 0.5-20%. The mass proportion of the negative electrode active material in the negative electrode material affects the capacity of the battery cell. When the mass proportion of the negative electrode active material is less than 0.5%, the negative electrode active material does not match the positive electrode active material, which will increase the probability of sodium precipitation, reduce the capacity of the battery, and reduce the number of battery cycles. When the proportion of the negative electrode active material is greater than 20%, the negative electrode active material is too much, which affects the proportion of other components, reduces the sodium supplement effect, the catalytic effect, and the conductive effect, thereby reducing the capacity of the battery. Optionally, the mass proportion of the negative electrode active material in the negative electrode material is 1-10%.

[0017] In any embodiment, the sodium supplement includes at least one of Na2O, Na2CO3, NaF, Na2MnO4, Na3Co(CO3)2, Na3VO4 and Na2S. Using at least one of the above sodium supplements can have a good sodium supplement effect and improve the initial efficiency of the battery cell.

[0018] In any embodiment, the negative electrode active material includes at least one of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal frameworks, titanium oxides and silicon oxides. Using at least one of the above negative electrode active materials can better match the positive electrode material and improve the capacity of the battery.

[0019] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode material, which is used to prepare the negative electrode material of the first aspect of the present application, comprising the following steps:

[0020] The material of the core is mixed with the solution of the coating layer material, granulated, and calcined to obtain the negative electrode material.

[0021] By mixing the core material with a solution of the coating layer material, granulating, and calcining, the coating layer material can be at least partially coated on the surface of the core material to obtain a negative electrode material with a core-shell structure. The core-shell structure is formed by granulating the mixed solution, and the coating layer is more evenly coated on the surface of the core, thereby improving the protection of the core material.

[0022] In some embodiments of the present application, the solvent in the solution of the coating material may be a volatile solvent, which is removed in a subsequent step, for example, it may be one or a combination of cyclohexane, ethanol, ether, N-methylpyrrolidone (NMP), and acetone.

[0023] In any embodiment, the step of mixing the core material with the solution of the coating layer material, granulating, and calcining to obtain the negative electrode material comprises:

[0024] The material of the inner core is mixed with the solution of the sodium supplementing agent, granulated, and calcined to obtain a first precursor of the inner core coated with the sodium supplementing agent;

[0025] The first precursor of the inner core coated with the sodium supplement agent is mixed with the solution of the outer coating layer material, granulated, and calcined to obtain the negative electrode material.

[0026] The material of the inner core is mixed with a solution of a sodium supplement, granulated, and calcined to obtain a first precursor of the inner core coated with the sodium supplement; the first precursor of the inner core coated with the sodium supplement is mixed with a solution of an outer coating layer material, granulated, and calcined to obtain a negative electrode material. A negative electrode material consisting of two coating layers can be obtained, wherein the sodium supplement is located in the middle coating layer.

[0027] In any embodiment, the step of mixing the first precursor of the sodium supplementing agent coated inner core with the solution of the outer coating layer material, granulating, and calcining to obtain the negative electrode material comprises:

[0028] The amorphous carbon solution is mixed with the first precursor of the sodium supplementing agent coating the inner core, the conductive agent solution and the boron compound solution, granulated and calcined to obtain the negative electrode material.

[0029] The negative electrode material is obtained by mixing an amorphous carbon solution with a first precursor of a sodium supplementer coated inner core, a conductive agent solution and a boron-containing compound solution, granulating and calcining. The sodium supplementer coated inner core can be more evenly mixed in the conductive agent, the boron-containing compound and the amorphous carbon solution. After spray drying, a core-shell structured negative electrode material with two more evenly coated layers is obtained.

[0030] In any embodiment, the steps of mixing the core material with the solution of the coating layer material, granulating, and calcining to obtain the negative electrode material include:

[0031] The conductive agent solution, the boron-containing compound and the sodium supplement agent are mixed with the amorphous carbon solution, heated for reaction, filtered, freeze-dried, crushed, and configured into a solution to obtain a precursor composite material solution;

[0032] Graphite is added to a solution of a precursor composite material, spray-dried, and calcined under an inert atmosphere to obtain a negative electrode material.

[0033] By mixing the conductive agent solution, the boron-containing compound and the sodium supplementer with the amorphous carbon solution, the conductive agent, the boron-containing compound, the sodium supplementer and the amorphous carbon can be mixed more evenly in the solution, and then graphite is added and spray-dried to obtain a negative electrode material with a more evenly coated core-shell structure.

[0034] In some embodiments of the present application, a conductive agent solution, a boron-containing compound and a sodium supplement are mixed with an amorphous carbon solution, heated to react, filtered, freeze-dried, crushed, and configured into a solution to obtain a solution of a precursor composite material. The solvent of the solution of the precursor composite material can be carbon tetrachloride, N-methylpyrrolidone, or cyclohexane.

[0035] In some embodiments of the present application, the conductive agent solution may use an oil-based conductive agent, and N-methylpyrrolidone may be used as a solvent to dissolve the conductive agent into a conductive agent solution with a mass concentration of 0.5 to 5 wt %.

[0036] In any embodiment, the steps of mixing the conductive agent solution, the boron-containing compound and the sodium supplement with the amorphous carbon solution, heating for reaction, filtering, freeze-drying, crushing, and configuring into a solution to obtain a precursor composite material solution,

[0037] The temperature of the heating reaction is 100-300°C. The heating step can remove the solvent. When the heating temperature is less than 100°C, the amount of residual solvent is too much, which reduces the energy density of the battery. When the temperature is greater than 300°C, the probability of side reactions between the active substance and the solvent will increase, generating inert substances that cannot be used, which reduces the energy density of the battery. Optionally, the heating temperature is 150-250°C; and / or,

[0038] The heating reaction time is 0.5 to 8 hours. If the reaction time is less than 0.5 hours, the residual solvent is too much, which reduces the energy density of the battery. If the reaction time is more than 8 hours, the probability of side reactions between the active substance and the solvent will increase, generating inert substances that cannot be used, which reduces the energy density of the battery. Optionally, the heating reaction time is 1 to 6 hours.

[0039] In any embodiment, the step is to add graphite to a solution of a precursor composite material, spray dry, and calcine under an inert atmosphere to obtain a negative electrode material.

[0040] The calcination temperature is 500-1500°C. If the calcination temperature is less than 500°C, the calcination is incomplete and the mechanical strength of the carbide is weak. If the calcination temperature is greater than 1500°C, the graphite in the carbonized product tends to be ordered and the porosity decreases. Optionally, the calcination temperature is 600-1000°C; and / or,

[0041] The calcination time is 0.5 to 8 hours. If the calcination time is less than 0.5 hours, the internal carbonization of the amorphous carbon is insufficient. If the calcination time is greater than 8 hours, within a certain calcination range, the voids in the carbonized material will basically not change. Too long a time will affect production capacity. Optionally, the calcination time is 1 to 6 hours.

[0042] In a third aspect, an embodiment of the present application provides a negative electrode sheet, comprising the negative electrode material of the first aspect of the present application.

[0043] In a fourth aspect, an embodiment of the present application provides an electrochemical device, comprising the negative electrode sheet of the third aspect of the present application.

[0044] In any embodiment, the electrochemical device comprises a capacitor, a primary battery, or a secondary battery.

[0045] In a fifth aspect, an embodiment of the present application proposes an electrical device, including the electrochemical device of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0047] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0048] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0049] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0050] Figure 5 yes Figure 4An exploded view of a battery pack according to an embodiment of the present application is shown.

[0051] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0052] Description of reference numerals:

[0053] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION

[0054] The following specifically discloses the negative electrode material, the method for preparing the negative electrode material, the negative electrode sheet, the electrochemical device and the electric device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0058] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] In order to meet the fast charging performance of new energy vehicles, many energy materials with high energy density and fast charging performance have been developed one after another. Among them, sodium-ion batteries are regarded as one of the substitutes for lithium-ion batteries due to their abundant sodium resources, low price and superior safety performance.

[0060] In order to reduce the irreversible sodium loss during the first charge and discharge and improve the energy density of the battery, sodium replenishment has become a research focus. However, the conventional sodium replenishment method is mainly aimed at the sodium replenishment of the positive electrode active material, which has no obvious effect on improving the fast charging performance, and has problems such as low first efficiency and poor cycle performance. In addition, when the negative electrode active material comes into contact with the electrolyte, some of the negative electrode active materials undergo irreversible reactions, producing inert materials that cannot participate in electron transmission, reducing the proportion of negative electrode active materials, thereby reducing the energy density and first charge and discharge efficiency of the battery.

[0061] Therefore, there are endless studies on sodium supplementation technology and improving the energy density of battery cells. For example, a sodium vanadium phosphate-carbon core-shell nanorod, preparation method and application, which consists of internal sodium vanadium phosphate particles and an externally coated graphitized carbon layer; the small size and large specific surface area are conducive to the infiltration and transmission of the electrolyte, and can buffer the Na during the charge and discharge process. + The strain generated during the embedding / ejection process can promote the transfer of ions and electrons during the charge and discharge process. However, in the above scheme, the negative electrode active material is coated with the sodium supplement, which makes the release of sodium in the sodium supplement more difficult, which is not conducive to sodium supplementation. In addition, the negative electrode active material is in the outer shell and directly contacts the electrolyte, which is prone to irreversible reactions.

[0062] Unexpectedly, the material of the inner core includes the negative electrode active material, the material of the coating layer includes the sodium supplement agent, and the coating layer is at least partially coated on the surface of the inner core, which can improve the efficiency of sodium supplementation and reduce the irreversible reaction between the negative electrode active material and the electrolyte, thereby improving the energy density and the initial charge and discharge efficiency of the battery cell.

[0063] Based on this, the present application provides a negative electrode material and a preparation method thereof, a negative electrode sheet and an electrochemical device.

[0064] In a first aspect, an embodiment of the present application proposes a negative electrode material, comprising a core and a coating layer at least partially coating the surface of the core, wherein the material of the core comprises a negative electrode active material, and the material of the coating layer comprises a sodium supplement.

[0065] Therefore, in the technical solution of the embodiment of the present application, by at least partially coating the surface of the inner core including the negative electrode active material with the sodium supplement, on the one hand, the irreversible sodium loss of the first charge and discharge can be compensated by the sodium supplement, the consumption of the sodium source can be reduced, and the first efficiency and cycle performance of the battery cell can be improved. On the other hand, by at least partially coating the sodium supplement, the direct contact between the negative electrode active material and the electrolyte can be reduced, thereby reducing the irreversible reaction between the negative electrode active material and the electrolyte, thereby improving the energy density and the first charge and discharge efficiency of the battery cell. In some embodiments of the present application, the coating layer may be partially coated on the surface of the inner core; in other embodiments of the present invention, the coating layer may be completely coated on the surface of the inner core. At this time, the coating layer has a better protective effect on reducing the direct contact between the inner core negative electrode active material and the electrolyte.

[0066] In any embodiment, the material of the coating layer also includes at least one of a conductive agent, amorphous carbon and a boron-containing compound. By adding a conductive agent to the material of the coating layer, multiple conductive channels can be formed in the coating layer, the transmission efficiency of sodium ions in the sodium supplement material is improved, and additional electron channels are provided for the negative electrode active material in the core, thereby improving the transmission efficiency of electrons, and thus improving the rate performance of the battery cell. By adding amorphous carbon to the material of the coating layer, a large-area conductive channel can be formed in the entire coating layer, the transmission efficiency of sodium ions in the sodium supplement material is improved, and electron channels are provided for the negative electrode active material in the core, thereby improving the transmission efficiency of electrons, and thus improving the rate performance of the battery cell. By adding a boron-containing compound to the coating layer material, the catalytic properties of the boron-containing compound can be utilized to improve the ability of the sodium supplement agent to release sodium ions at a lower potential, thereby improving the sodium supplement efficiency of the negative electrode material, thereby improving the first charge and discharge efficiency. In some embodiments of the present application, the material of the coating layer may include only any one of a conductive agent, amorphous carbon, and a boron-containing compound. In some embodiments of the present application, the material of the coating layer also includes two or more of a conductive agent, amorphous carbon, and a boron-containing compound. In some embodiments of the present application, the coating layer can be a mixed layer, and the material of the mixed layer includes a sodium supplement and also includes a conductive agent, amorphous carbon, and at least one of a boron-containing compound. In some embodiments of the present application, the coating layer can also be a multilayer, for example, the material of the middle layer includes a sodium supplement, and the material of the outer layer includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound.

[0067] It should be noted that when the material of the coating layer includes a conductive agent, in some embodiments of the present application, the specific type of the conductive agent is not limited, as long as multiple conductive channels can be formed to provide channels for the transfer of sodium ions and electrons. For example, the conductive agent can be carbon nanotubes, graphene or conductive carbon black. When the material of the coating layer includes amorphous carbon, in some embodiments of the present application, the material of the coating layer may only contain amorphous carbon and sodium-supplementing materials. In other embodiments of the present application, the material of the coating layer may simultaneously contain amorphous carbon, a conductive agent and a sodium-supplementing material. When amorphous carbon, a conductive agent and a sodium-supplementing material are simultaneously contained, a plurality of conductive channel points can be provided while providing a large area of ​​conductive channels for the coating layer. The combination of the conductive channel surface and the conductive channel point can further improve the transmission efficiency of sodium ions in the sodium-supplementing material, provide enough electron channels for the negative electrode active material in the inner core, further improve the transmission efficiency of electrons, and thus improve the rate performance of the battery cell. In some embodiments of the present application, the specific type of the amorphous carbon is not limited, as long as it can form a large-area conductive channel to provide a surface channel for the transfer of sodium ions and electrons. For example, the amorphous carbon can be epoxy resin, asphalt, phenolic resin, gelatin, furfural resin, etc.

[0068] In any embodiment, the coating layer includes an intermediate coating layer and an outer coating layer sequentially arranged from the inner core to the outer core, wherein the material of the intermediate coating layer includes a sodium supplement, and the material of the outer coating layer includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound. By setting the sodium supplement as the intermediate coating layer and at least one of the conductive agent, amorphous carbon, and a boron-containing compound as the outer coating layer, the sodium supplement can be protected under the premise of reducing the direct contact between the inner core negative electrode active material and the electrolyte, reducing the direct contact between the sodium supplement and the electrolyte, and improving the sodium supplement effect. At the same time, since the outer coating layer includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound, the sodium supplement performance of the sodium supplement can be improved. In some embodiments of the present application, the material of the outer coating layer may include only any one of a conductive agent, amorphous carbon, and a boron-containing compound. In some embodiments of the present application, the material of the outer coating layer may include two or more of a conductive agent, amorphous carbon, and a boron-containing compound.

[0069] In any embodiment, the conductive agent includes at least one of conductive carbon black, carbon nanotubes and graphene. The conductive channel formed by at least one of conductive carbon black, carbon nanotubes and graphene has better conductivity and is more effective in improving the rate performance of the battery cell; and / or,

[0070] In any embodiment, the amorphous carbon includes at least one of epoxy resin, phenolic resin and furfural resin. Using at least one of epoxy resin, phenolic resin and furfural resin can reduce the cost of the coating layer on the basis of providing a conductive channel surface; and / or,

[0071] In any embodiment, the boron-containing compound includes at least one of titanium diboride, magnesium diboride, zirconium diboride and tungsten boride. Using at least one of titanium diboride, magnesium diboride, zirconium diboride and tungsten boride can provide better catalytic performance, further improve the ability of the sodium supplement agent to release sodium ions at a lower potential, thereby improving the sodium supplement efficiency of the negative electrode material, thereby improving the initial charge and discharge efficiency.

[0072] In any embodiment, the particle size of the boron-containing compound is 50 to 500 nm. The particle size of the boron-containing compound affects its catalytic performance. When the particle size is less than 50 nm, the particles are small, and the boron-containing compound is easy to agglomerate, which reduces its own dispersion performance, thereby affecting the catalytic effect. When the particle size is greater than 500 nm, the particles are large and the specific surface area is small, which reduces its own catalytic performance. The particle size of the boron-containing compound can be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm; optionally, the particle size of the boron-containing compound is 100 to 200 nm.

[0073] In any embodiment, the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon, wherein the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon in a mass ratio of (0.5-10):(0.5-10):(0.1-5):100. When the material of the coating layer contains a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon at the same time, a suitable mass ratio can improve the sodium supplement The ability of the agent to release sodium ions at a lower potential, thereby improving the sodium supplement efficiency of the negative electrode material, providing a conductive channel and a conductive surface for sodium ions and electrons, thereby improving the initial charge and discharge efficiency and improving the rate performance. When the mass ratio of the sodium supplement is less than 0.5, the proportion is too small, and the sodium supplement effect decreases. When the mass ratio of the sodium supplement is greater than 10, the sodium supplement occupies more volume, squeezing the proportion of other components, and the extra sodium supplement cannot be used, reducing the energy density of the battery cell. When the mass ratio of the conductive agent is less than 0.5, the conductive channel points are too few, and the improvement rate of the conductive performance is low. When the mass ratio of the conductive agent is greater than 10, the conductive agent is too much, and the volume occupied by the conductive agent is too large, squeezing the proportion of other components, and the extra conductive agent cannot be used, squeezing the proportion of other components. When the mass ratio of the boron-containing compound is less than 0.1, the content of the boron-containing compound is low, the catalytic effect is weak, and the catalytic performance decreases. When the mass ratio of the boron-containing compound is greater than 5, the boron-containing compound is too much, and the volume occupied by the boron-containing compound is too much, squeezing the proportion of other components, and the extra boron-containing compound cannot be used, reducing the energy density of the battery. Optionally, the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon in a mass ratio of: (1-5): (1-5): (0.5-2): 100.

[0074] In any embodiment, the mass proportion of the negative electrode active material in the negative electrode material is 0.5-20%, and the mass proportion of the negative electrode active material in the negative electrode material affects the capacity of the battery cell. When the proportion of the negative electrode active material is less than 0.5%, the negative electrode active material does not match the positive electrode active material, which will increase the probability of sodium precipitation, reduce the capacity of the battery, and reduce the number of battery cycles. When the proportion of the negative electrode active material is greater than 20%, the negative electrode active material is too much, which affects the proportion of other components, reduces the sodium supplement effect, the catalytic effect, and the conductive effect, thereby reducing the capacity of the battery. The mass proportion of the negative electrode active material in the negative electrode material can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. Optionally, the mass proportion of the negative electrode active material in the negative electrode material is 1-10%.

[0075] In any embodiment, the sodium supplement includes at least one of Na2O, Na2CO3, NaF, Na2MnO4, Na3Co(CO3)2, Na3VO4 and Na2S. Adopting at least one of the above sodium supplements can have a better sodium supplement effect and improve the initial efficiency of the battery cell. In some embodiments of the present application, the sodium supplement may contain only any one of Na2O, Na2CO3, NaF, Na2MnO4, Na3Co(CO3)2, Na3VO4 and Na2S. In other embodiments of the present application, the conductive agent may also contain two or more of Na2O, Na2CO3, NaF, Na2MnO4, Na3Co(CO3)2, Na3VO4 and Na2S at the same time.

[0076] In any embodiment, the negative electrode active material includes at least one of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal skeletons, titanium oxides and silicon oxides. The use of at least one of the above negative electrode active materials can better match the positive electrode material and improve the capacity of the battery. In some embodiments of the present application, the negative electrode active material may contain only any one of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal skeletons and titanium oxides. In other embodiments of the present application, the negative electrode active material may also contain two or more of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal skeletons and titanium oxides at the same time.

[0077] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode material, which is used to prepare the negative electrode material of the first aspect of the present application, comprising the following steps:

[0078] The material of the core is mixed with the solution of the coating layer material, granulated, and calcined to obtain the negative electrode material.

[0079] By mixing the core material with a solution of the coating layer material, granulating, and calcining, the coating layer material can be at least partially coated on the surface of the core material to obtain a negative electrode material with a core-shell structure. The core-shell structure is formed by granulating the mixed solution, and the coating layer is more evenly coated on the surface of the core, thereby improving the protection of the core material.

[0080] In some embodiments of the present application, the solvent in the solution of the coating material may be a volatile solvent, which is removed in a subsequent step, for example, it may be one or a combination of cyclohexane, ethanol, ether, N-methylpyrrolidone (NMP), and acetone.

[0081] In any embodiment, the step of mixing the core material with the solution of the coating layer material, granulating, and calcining to obtain the negative electrode material comprises:

[0082] The material of the inner core is mixed with the solution of the sodium supplementing agent, granulated, and calcined to obtain a first precursor of the inner core coated with the sodium supplementing agent;

[0083] The first precursor of the inner core coated with the sodium supplement agent is mixed with the solution of the outer coating layer material, granulated, and calcined to obtain the negative electrode material.

[0084] The material of the inner core is mixed with a solution of a sodium supplement, granulated, and calcined to obtain a first precursor of the inner core coated with the sodium supplement; the first precursor of the inner core coated with the sodium supplement is mixed with a solution of an outer coating layer material, granulated, and calcined to obtain a negative electrode material. A negative electrode material consisting of two coating layers can be obtained, wherein the sodium supplement is located in the middle coating layer.

[0085] In any embodiment, the step of mixing the first precursor of the sodium supplementing agent coated inner core with the solution of the outer coating layer material, granulating, and calcining to obtain the negative electrode material comprises:

[0086] The amorphous carbon solution is mixed with the first precursor of the sodium supplementing agent coating the inner core, the conductive agent solution and the boron compound solution, granulated and calcined to obtain the negative electrode material.

[0087] The negative electrode material is obtained by mixing an amorphous carbon solution with a first precursor of a sodium supplementer coated inner core, a conductive agent solution and a boron-containing compound solution, granulating and calcining. The sodium supplementer coated inner core can be more evenly mixed in the conductive agent, the boron-containing compound and the amorphous carbon solution. After spray drying, a core-shell structured negative electrode material with two more evenly coated layers is obtained.

[0088] In any embodiment, the steps of mixing the core material with the solution of the coating layer material, granulating, and calcining to obtain the negative electrode material include:

[0089] The conductive agent solution, the boron-containing compound and the sodium supplement agent are mixed with the amorphous carbon solution, heated for reaction, filtered, freeze-dried, crushed, and configured into a solution to obtain a precursor composite material solution;

[0090] Graphite is added to a solution of a precursor composite material, spray-dried, and calcined under an inert atmosphere to obtain a negative electrode material.

[0091] By mixing the conductive agent solution, the boron-containing compound and the sodium supplementer with the amorphous carbon solution, the conductive agent, the boron-containing compound, the sodium supplementer and the amorphous carbon can be mixed more evenly in the solution, and then graphite is added and spray-dried to obtain a negative electrode material with a more evenly coated core-shell structure.

[0092] In some embodiments of the present application, a conductive agent solution, a boron-containing compound and a sodium supplement are mixed with an amorphous carbon solution, heated to react, filtered, freeze-dried, crushed, and configured into a solution to obtain a solution of a precursor composite material. The solvent of the solution of the precursor composite material can be carbon tetrachloride, N-methylpyrrolidone, or cyclohexane.

[0093] In some embodiments of the present application, the conductive agent solution may use an oil-based conductive agent, and N-methylpyrrolidone may be used as a solvent to dissolve the conductive agent into a conductive agent solution with a mass concentration of 0.5 to 5 wt %.

[0094] In any embodiment, the steps of mixing the conductive agent solution, the boron-containing compound and the sodium supplement with the amorphous carbon solution, heating for reaction, filtering, freeze-drying, crushing, and configuring into a solution to obtain a precursor composite material solution,

[0095] The temperature of the heating reaction is 100-300°C. The heating step can remove the solvent. When the heating temperature is less than 100°C, the amount of residual solvent is too much, which reduces the energy density of the battery. When the temperature is greater than 300°C, the probability of side reactions between the active substance and the solvent will increase, generating inert substances that cannot be used, which reduces the energy density of the battery. The heating temperature can be 100°C, 120°C, 150°C, 180°C, 200°C, 230°C, 250°C, 270°C, 300°C. Optionally, the heating temperature is 150-250°C; and / or,

[0096] The heating reaction time is 0.5 to 8 hours. If the reaction time is less than 0.5 hours, the residual solvent is too much, which reduces the energy density of the battery. If the reaction time is more than 8 hours, the probability of side reactions between the active substance and the solvent will increase, and unusable inert substances will be generated, which reduces the energy density of the battery. The heating reaction time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, and 8 hours. Optionally, the heating reaction time is 1 to 6 hours.

[0097] In any embodiment, the step is to add graphite to a solution of a precursor composite material, spray dry, and calcine under an inert atmosphere to obtain a negative electrode material.

[0098] The calcination temperature is 500-1500°C. If the calcination temperature is less than 500°C, the calcination is incomplete and the mechanical strength of the carbide is weak. If the calcination temperature is greater than 1500°C, the graphite in the carbonized product tends to be ordered and the porosity decreases. The calcination temperature can be 500°C, 600°C, 700°C, 750°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C. Optionally, the calcination temperature is 600-1000°C; and / or,

[0099] The calcination time is 0.5 to 8 hours. If the calcination time is less than 0.5 hours, the internal carbonization of the amorphous carbon is insufficient. If the calcination time is greater than 8 hours, within a certain calcination range, the voids in the carbonized material will basically not change. Too long a time will affect the production capacity. 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h. Optionally, the calcination time is 1 to 6 hours.

[0100] In a third aspect, an embodiment of the present application provides a negative electrode sheet, comprising the negative electrode material of the first aspect of the present application.

[0101] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0102] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0103] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0104] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0105] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0106] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0107] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0108] In a fourth aspect, an embodiment of the present application provides an electrochemical device, comprising the negative electrode sheet of the third aspect of the present application.

[0109] In any embodiment, the electrochemical device comprises a capacitor, a primary battery, or a secondary battery.

[0110] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0111] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0112] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0113] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0114] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0115] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0116] In some embodiments, reference Figure 2, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0117] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0118] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0119] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0120] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0121] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0122] In a fifth aspect, an embodiment of the present application proposes an electrical device, including the electrochemical device of the fourth aspect of the present application.

[0123] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0124] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0125] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0126] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0127] Example

[0128] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0129] The parameters of the negative electrode materials of Examples 1 to 21 of the present application and Comparative Examples 1 to 2 are according to the parameters in Table 1.

[0130]

[0131] Embodiment 22

[0132] The difference between Example 22 and Example 21 is that the coating layer of Example 22 consists of an intermediate coating layer and an outer coating layer, wherein the intermediate coating layer is Na3VO4, and the outer coating layer consists of carbon nanotubes, epoxy resin and titanium diboride, and other parameters are the same as Example 21. The first efficiency of Example 22 is 96.5%, the 200 cycle retention rate is 90.5%, and the 3C rate performance is 98.3%.

[0133] Embodiment 23

[0134] A method for preparing a negative electrode material comprises the following steps:

[0135] The material of the core is mixed with the solution of the coating layer material, granulated, and calcined to obtain the negative electrode material.

[0136] Embodiment 24

[0137] A method for preparing a negative electrode material comprises the following steps:

[0138] The conductive agent solution, the boron-containing compound and the sodium supplement agent are mixed with the amorphous carbon solution, heated for reaction, filtered, freeze-dried, crushed, and configured into a solution to obtain a precursor composite material solution;

[0139] Graphite is added to a solution of a precursor composite material, spray-dried, and calcined under an inert atmosphere to obtain a negative electrode material.

[0140] Embodiment 25

[0141] A method for preparing a negative electrode material comprises the following steps:

[0142] The conductive agent solution, the boron-containing compound and the sodium supplement agent are mixed with the amorphous carbon solution, heated at 200° C. for 3 hours, filtered, freeze-dried, crushed, and configured into a solution to obtain a precursor composite material solution;

[0143] Graphite is added to a solution of a precursor composite material, spray dried, and calcined at 800° C. for 4 hours under an inert atmosphere to obtain a negative electrode material.

[0144] Embodiment 26

[0145] A method for preparing a negative electrode material comprises the following steps:

[0146] The conductive agent solution, the boron-containing compound and the sodium supplement agent are mixed with the amorphous carbon solution, wherein the mass ratio of the sodium supplement agent: the conductive agent: the boron-containing compound: the amorphous carbon is 8:8:1.5:100, heated at 200° C. for reaction for 3 hours, filtered, freeze-dried, crushed, and configured into a solution to obtain a solution of a precursor composite material;

[0147] Graphite is added to a solution of a precursor composite material, spray dried, and calcined at 800° C. for 4 hours under an inert atmosphere to obtain a negative electrode material, wherein the mass proportion of graphite in the negative electrode material is 10%.

[0148] Performance Testing

[0149] The negative electrode materials of Examples 1 to 22 and Comparative Examples 1 to 2 were stirred into slurries according to the ratio of negative electrode material: binder (LA132): conductive agent (SP): solvent = 95 g: 1 g: 4 g: 220 mL, and coated on the anode current collector (copper foil). After drying and cold pressing, the negative electrode sheets were obtained. LiPF6 / EC+DEC is the electrolyte, celegard2400 is the separator, sodium vanadium phosphate is the positive electrode material (positive electrode active material: binder (PVDF): conductive agent (conductive carbon black) is fully stirred in a certain amount of solvent N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and the positive electrode slurry is obtained after mixing evenly; the positive electrode slurry is then evenly coated on the positive electrode collector (aluminum foil), and the positive electrode sheet is obtained after drying, cold pressing, and cutting). In a vacuum glove box, the positive electrode sheet, separator, and negative electrode sheet are stacked in sequence according to the positive electrode shell-positive electrode sheet-electrolyte-diaphragm-negative electrode sheet-negative electrode shell, and assembled into a sodium ion full battery in sequence for the following tests:

[0150] Electrical performance test

[0151] First efficiency: The battery was charged and discharged for the first time at a charge rate of 0.1C in the voltage range of 0.005-2.0V. First efficiency = first discharge capacity / first charge capacity. The test results are shown in Table 1.

[0152] Cyclic performance test: At ambient temperature (25°C), with a charge rate of 1 / 3C and a discharge rate of 1C, the battery was cycled for 300 cycles within a voltage range of 2.8-4.2V; the first discharge capacity was recorded as C0, and the capacity retention rate Pn of each subsequent discharge cycle was calculated according to the following formula:

[0153] Pn=Cn / C0*100%

[0154] Rate performance test: At ambient temperature (25°C), charge to 4.3V at a constant current rate of 1 / 3C, leave for 5 minutes, and then discharge to 2.8V at different rates (1C / 2C / 3C), and cycle 300 times; the 1C discharge capacity is taken as D0, and the capacity retention rate Qn of each subsequent battery rate discharge is calculated according to the following formula:

[0155] Qn=(Dn / D0)×100%

[0156] The statistical experimental results are shown in Table 1.

[0157] As can be seen from Table 1, it can be seen from Examples 1 to 3 and Comparative Examples 1 to 2 that by at least partially coating the surface of the inner core including the negative electrode active material with the sodium supplement agent, the irreversible sodium loss of the first charge and discharge can be compensated by the sodium supplement agent, the consumption of the sodium source can be reduced, and the first efficiency and cycle performance of the battery cell can be improved. The sodium supplement agent can compensate for the irreversible sodium loss of the first charge and discharge, reduce the consumption of the sodium source, and improve the first efficiency and cycle performance of the battery cell. Comparative Example 1 does not use the sodium supplement agent to coat the negative electrode active material, and Comparative Example 2 only uses physical mixing and does not form a coating layer. The negative electrode active material will still be in direct contact with the electrolyte, affecting the efficiency of the battery. The electrical properties of Examples 1 to 3 are all better than those of Comparative Examples 1 and 2.

[0158] It can be seen from Examples 4 to 6 that by adding a conductive agent to the material of the coating layer, multiple conductive channels can be formed in the coating layer, thereby improving the transmission efficiency of sodium ions in the sodium supplement material, and at the same time providing additional electron channels for the negative electrode active material in the core, thereby improving the electron transmission efficiency and thus improving the rate performance of the battery cell.

[0159] It can be seen from Examples 7 to 9 that by adding amorphous carbon to the material of the coating layer, a large-area conductive channel can be formed in the entire coating layer, thereby improving the transmission efficiency of sodium ions in the sodium supplement material, and at the same time providing an electron channel for the negative electrode active material in the core, thereby improving the electron transmission efficiency and thus improving the rate performance of the battery cell.

[0160] It can be seen from Examples 10 to 14 that by adding boron-containing compounds to the coating layer material, the catalytic properties of the boron-containing compounds can be utilized to improve the ability of the sodium replenisher to release sodium ions at a lower potential, thereby improving the sodium replenishment efficiency of the negative electrode material, thereby improving the initial charge and discharge efficiency.

[0161] It can be seen from Examples 15 to 21 that when the material of the coating layer contains a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon at the same time, a suitable mass ratio can improve the sodium supplement The ability of the sodium supplement to release sodium ions at a relatively low potential, thereby improving the sodium supplement efficiency of the negative electrode material, and providing a conductive channel and a conductive surface for sodium ions and electrons, thereby improving the first charge and discharge efficiency, and improving the rate performance. When the mass ratio of the sodium supplement is less than 0.5, the proportion is small, and the sodium supplement effect decreases. When the mass ratio of the sodium supplement is greater than 10, the sodium supplement occupies more volume, squeezing the proportion of other components, and the extra sodium supplement cannot be used, reducing the energy density of the battery. When the mass ratio of the conductive agent is less than 0.5, the conductive channel point is small, and the improvement rate of the conductive performance is low. When the mass ratio of the conductive agent is greater than 10, the conductive agent is more, and the conductive agent occupies a larger volume, squeezing the proportion of other components, and the extra conductive agent cannot be used, squeezing the proportion of other components. When the mass ratio of boron-containing compounds is less than 0.1, the content of boron-containing compounds is low, the catalytic effect is weak, and the catalytic performance decreases. When the mass ratio of boron-containing compounds is greater than 5, the amount of boron-containing compounds is large, and the boron-containing compounds occupy more volume, squeezing the proportion of other components, and the excess boron-containing compounds cannot be used, reducing the energy density of the battery cell.

[0162] It can be seen from Examples 21 and 22 that by setting the sodium supplementer as the intermediate coating layer and setting at least one of the conductive agent, amorphous carbon and boron-containing compounds as the outer coating layer, the sodium supplementer can be protected while reducing the direct contact between the inner core negative electrode active material and the electrolyte, reducing the direct contact between the sodium supplementer and the electrolyte and improving the sodium supplement effect. At the same time, since the outer coating layer includes at least one of the conductive agent, amorphous carbon and boron-containing compounds, the sodium supplement performance of the sodium supplementer can be improved.

[0163] It can be seen from Examples 1 to 3 that the mass proportion of the negative electrode active material in the negative electrode material affects the capacity of the battery cell. When the proportion of the negative electrode active material is less than 0.5%, the negative electrode active material does not match the positive electrode active material, which will increase the probability of sodium precipitation, reduce the capacity of the battery, and reduce the number of battery cycles. When the proportion of the negative electrode active material is greater than 20%, the negative electrode active material is too much, which affects the proportion of other components, reduces the sodium supplementation effect, the catalytic effect, and the conductive effect, thereby reducing the capacity of the battery.

[0164] In summary, in the negative electrode material proposed in the present application, the sodium supplement agent is at least partially coated on the surface of the inner core including the negative electrode active material. On the one hand, the sodium supplement agent can make up for the irreversible sodium loss of the first charge and discharge, reduce the consumption of the sodium source, and improve the first efficiency and cycle performance of the battery. On the other hand, by at least partially coating the sodium supplement agent, the direct contact between the negative electrode active material and the electrolyte can be reduced, thereby reducing the irreversible reaction between the negative electrode active material and the electrolyte, thereby improving the energy density and the first charge and discharge efficiency of the battery.

[0165] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A negative electrode material, characterized in that: It comprises a core and a coating layer at least partially coating the surface of the core, wherein the material of the core comprises a negative electrode active material, and the material of the coating layer comprises a sodium supplement.

2. The negative electrode material according to claim 1, characterized in that The material of the coating layer further includes at least one of a conductive agent, amorphous carbon, and a boron-containing compound.

3. The negative electrode material according to claim 1 or 2, characterized in that The coating layer comprises an intermediate coating layer and an outer coating layer which are sequentially arranged from the inner core to the outer core, wherein the material of the intermediate coating layer comprises a sodium supplement, and the material of the outer coating layer comprises at least one of a conductive agent, amorphous carbon and a boron-containing compound.

4. The negative electrode material according to claim 2 or 3, characterized in that The conductive agent includes at least one of conductive carbon black, carbon nanotubes and graphene; and / or, The amorphous carbon comprises at least one of epoxy resin, phenolic resin and furfural resin; and / or, The boron-containing compound includes at least one of titanium diboride, magnesium diboride, zirconium diboride and tungsten boride.

5. The negative electrode material according to claim 3 or 4, characterized in that The particle size of the boron-containing compound is 50 to 500 nm; optionally, the particle size of the boron-containing compound is 100 to 200 nm.

6. The negative electrode material according to any one of claims 1 to 5, characterized in that The material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon, wherein the mass ratio of the sodium supplement, the conductive agent, the boron-containing compound and the amorphous carbon is: (0.5-10):(0.5-10):(0.1-5):100; optionally, the material of the coating layer includes a sodium supplement, a conductive agent, a boron-containing compound and amorphous carbon in a mass ratio of: (1-5):(1-5):(0.5-2):

100.

7. The negative electrode material according to any one of claims 1 to 6, characterized in that The negative electrode active material accounts for 0.5 to 20% by mass of the negative electrode material. Optionally, the negative electrode active material accounts for 1 to 10% by mass of the negative electrode material.

8. The negative electrode material according to any one of claims 1 to 7, characterized in that The sodium supplement includes at least one of Na2O, Na2CO3, NaF, Na2MnO4, Na3Co(CO3)2, Na3VO4 and Na2S.

9. The negative electrode material according to any one of claims 1 to 8, characterized in that The negative electrode active material includes at least one of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal frameworks, titanium oxides and silicon oxides.

10. A method for preparing a negative electrode material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The material of the core is mixed with the solution of the coating layer material, granulated, and calcined to obtain the negative electrode material.

11. The method for preparing the negative electrode material according to claim 10, characterized in that: The steps of mixing the core material with the solution of the coating layer material, granulating, and calcining to obtain the negative electrode material include: The material of the inner core is mixed with the solution of the sodium supplementing agent, granulated, and calcined to obtain a first precursor of the inner core coated with the sodium supplementing agent; The first precursor of the inner core coated with the sodium supplement agent is mixed with the solution of the material of the outer coating layer, granulated, and calcined to obtain the negative electrode material.

12. The method for preparing the negative electrode material according to claim 11, characterized in that: The steps of mixing the first precursor of the inner core coated with the sodium supplement agent with the solution of the outer coating layer material, granulating, and calcining to obtain the negative electrode material include: The amorphous carbon solution is mixed with the first precursor of the sodium supplementing agent coating the inner core, the conductive agent solution and the boron compound solution, granulated and calcined to obtain the negative electrode material.

13. The method for preparing the negative electrode material according to claim 10, characterized in that: The steps of mixing the core material with the solution of the coating layer material, granulating, and calcining to obtain the negative electrode material include: The conductive agent solution, the boron-containing compound and the sodium supplement agent are mixed with the amorphous carbon solution, heated for reaction, filtered, freeze-dried, crushed, and configured into a solution to obtain a precursor composite material solution; Graphite is added to a solution of a precursor composite material, spray-dried, and calcined under an inert atmosphere to obtain a negative electrode material.

14. The method for preparing the negative electrode material according to claim 13, characterized in that: The steps are as follows: mixing the conductive agent solution, the boron-containing compound and the sodium supplement with the amorphous carbon solution, heating for reaction, filtering, freeze-drying, crushing, and preparing a solution to obtain a precursor composite material solution. The heating reaction temperature is 100-300°C; optionally, the heating temperature is 150-250°C; and / or, The heating reaction time is 0.5 to 8 hours; optionally, the heating reaction time is 1 to 6 hours.

15. The method for preparing the negative electrode material according to claim 13 or 14, characterized in that: Step: adding graphite to a solution of a precursor composite material, spray drying, and calcining under an inert atmosphere to obtain a negative electrode material. The calcination temperature is 500-1500°C; optionally, the calcination temperature is 600-1000°C; and / or, The calcination time is 0.5 to 8 hours; optionally, the calcination time is 1 to 6 hours.

16. A negative electrode sheet, characterized in that: The invention comprises a negative electrode material as claimed in any one of claims 1 to 9 or a negative electrode material prepared by the method for preparing the negative electrode material as claimed in any one of claims 10 to 15.

17. An electrochemical device, characterized in that: Comprising the negative electrode sheet as claimed in claim 16.

18. An electrical device, characterized in that: Comprising the negative electrode sheet as claimed in claim 16.

Citation Information

Patent Citations

  • Negative electrode material and preparation method and application thereof

    CN115000389A

  • Negative electrode material, negative electrode plate and sodium ion battery

    CN115275191A

  • Sodium-ion battery carbon-based negative electrode material and preparation method thereof

    CN115966666A

  • Sodium-ion battery negative electrode material, preparation method of negative electrode plate and sodium-ion battery

    CN116072994A

  • Modified hard carbon negative electrode material for sodium ion battery and preparation method of modified hard carbon negative electrode material

    CN116154175A